BELENGGU RASIONALITAS DALAM TAFSĪR BI AL-MA’THŪR: REKONSTRUKSI DIKOTOMIS ATAS SUMBER PENAFSIRAN - Mahbub Ghozali (REVELATIA: Jurnal Ilmu Al-Qur'`an dan Tafsir, 2021)
The Interpretation with transmitted text (riwāyah) which uses to get meaning far away from the influence of ratio (al-ra'y) still cannot occur. Various different narrations for interpreting the same verse in the exegesis via narration (al-tafsīr bi al-ma'thūr) can be evidence of the use of ijtihad in that interpretation model. In this context, this study aims to find evidence and reconceptualize the terms to prove the existence ratio on exegesis via narration. This study uses a qualitative method with the type of study that uses literature research and uses content analysis as an analytical tool. This study finds that the interpreters in the category of exegesis via narration used ratio in the form of transmitted text selection to strengthen the meaning desired. The unawareness of the existence of rationality in the exegesis via narration is caused by the confusion of the terms used which are borrowed from the term of hadith study (muṣṭalah al-ḥadīth). Based on this, this study proposes to redefine that term to illustrate that dichotomy does not refer to the use of transmitted text or ratios in interpretation, but that dichotomy occurs from the proximity of the resulting message to the literal meaning content in interpretation.